The spirit of the Blitz : home intelligence and British morale, September 1940 - June 1941 - Addison, Paul 1943-2020 Herausgeber; Crang, Jeremy 1961- Herausgeber (Oxford University Press, 2020)
Edited and introduced by two leading historians of the period, this volume tells the inside story of Home Intelligence and why it proved so controversial in Whitehall, the complete and unabridged sequence of reports provide us with a unique and extraordinary window into the mindset of the British during a momentous period in their history